Images of Ultrasonography or Abdominal Computed Tomography Scanning in Cases of Malignant Kidney Tumors - Muhammad Hidayat Surya Atmaja; Bambang Soeprijanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The malignant kidney tumor is a urinary tract tumor with the highest mortality and morbiditycompared to other urinary tract tumors. The role of USG radiology and CT scan is essential for diagnosingmalignant kidney tumors.Objective: To examine the diagnostic value of USG radiology and CT scan in diagnosing malignancy ofkidney tumor and its accuracy in assessing renal tumor operability.Methods: This study was a retrospective observational study using secondary data of radiologicalexamination including ultrasonography, CT scan and other postoperative results derived from medicalrecords. Data analysis was conducted descriptively.Results: The sensitivity score of USG, CT scan, and USG and CT scan was 60%, 82%, and 83% respectively.Sensitivity value of ultrasound examination was 60% and CT Scan was 82%. The incompatibility ofultrasound with pathology results was found in the case of hydronephrosis with the stone of 64%, stone of18%, cyst of 18 %, on CT Scan hydronephrosis with stone (83%) Pyelonephritis (17%). The incompatibilityof USG and CT Scan with operating results was 8%.Conclusion: Incompatibility of USG results with anatomic pathology results was found in cases ofhydronephrosis accompanied by stones, kidney stones, and benign lesions (cysts). Incompatibility of CTScan results with anatomic pathology results was found in cases of hydronephrosis accompanied by stoneand pyelonephritis.